2019
DOI: 10.1093/deafed/enz019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Accuracy in the Speech of Bimodal Bilingual Children with CIs

Abstract: Sign language use in the (re)habilitation of children with cochlear implants (CIs) remains a controversial issue. Concerns that signing impedes spoken language development are based on research comparing children exposed to spoken and signed language (bilinguals) to children exposed only to speech (monolinguals), although abundant research demonstrates that bilinguals and monolinguals differ in language development. We control for bilingualism effects by comparing bimodal bilingual (signing-speaking) children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…A qualitative data analysis showed that some participants had difficulties with correct adjective and adverb congruence, such as han sov djup, “he slept deep” instead of han sov djupt , “he slept deeply.” The grammatical constructions that included incorrect affixes were not numerous, but were noticeable. Similar findings of morphological difficulties have been described among populations of sign-print ( Schönström, 2010 ), sign-spoken bilingual DHH ( Goodwin & Lillo-Martin, 2019 ), and typically hearing L2 learners of Swedish and English ( Eklund-Heinonen, 2009 ).…”
Section: Discussionsupporting
confidence: 76%
“…A qualitative data analysis showed that some participants had difficulties with correct adjective and adverb congruence, such as han sov djup, “he slept deep” instead of han sov djupt , “he slept deeply.” The grammatical constructions that included incorrect affixes were not numerous, but were noticeable. Similar findings of morphological difficulties have been described among populations of sign-print ( Schönström, 2010 ), sign-spoken bilingual DHH ( Goodwin & Lillo-Martin, 2019 ), and typically hearing L2 learners of Swedish and English ( Eklund-Heinonen, 2009 ).…”
Section: Discussionsupporting
confidence: 76%
“…Although the fitting of hearing devices such as hearing aid (HA) or cochlear implant (CI) can ameliorate challenges in early spoken language development, the actual auditory experience of individual children may vary significantly, depending on the age of hearing loss diagnosis, degree of hearing loss, time of HA and CI fitting, and aided hearing level, not to mention the heterogeneity in mode of communication and educational experience later in school. Many studies have revealed significant delays of DHH children in English morphosyntactic development, based on varied types of research evidence, such as error analysis of misconstructed inflected forms in spoken language production (e.g., Bowdrie et al, 2021;Goodwin & Lillo-Martin, 2019;Guo et al, 2013;Werfel et al, 2022) and writing/spelling (e.g., Apel & Masterson, 2015;Breadmore et al, 2012). Studies that measured (inflectional) morphological knowledge using experimental tasks likewise reported gaps between DHH students and age-matched hearing controls (e.g., Davies et al, 2020;Gaustad et al, 2002).…”
Section: Morphology Reading and Dhh Readersmentioning
confidence: 99%
“…For example, these studies have not included DHH children with fluent, early sign language input at home. When such children have been studied, the results have shown that spoken language and sign language can develop together, just as they do for hearing bimodal bilinguals (Davidson et al, 2014;Goodwin & Lillo-Martin, 2019;Hassanzadeh, 2012;Rinaldi & Caselli, 2014). Davidson and colleagues (2014) examined ASL and English language development for five DHH children with Deaf, signing parents, comparing them to a group of 20 hearing Coda children.…”
Section: Sign and Spoken Languagesmentioning
confidence: 99%